2020
DOI: 10.1007/s10113-020-01723-5
|View full text |Cite
|
Sign up to set email alerts
|

Towards environmentally sound intensification pathways for dairy development in the Tanga region of Tanzania

Abstract: The gap between milk demand and domestic supply in Tanzania is large and projected to widen. Meeting such demand through local production of affordable milk presents an opportunity to improve the welfare of producers and market agents through the income and employment generated along the value chain (VC). Efforts to maximize milk yields, production and profitability need to be balanced with long-term sustainability. We combined environmental and economic ex-ante impact assessments of four intervention scenario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
1
14
1
Order By: Relevance
“…Moreover, owing to the higher feed conversion efficiency and greater efficiency of Bos taurus genetics 88 , a greater uptake of Bos taurus in place of Bos indicus genetics could allow for milk production targets to be met with a smaller land and carbon footprint. Notenbaert et al 26 evaluated the role of genetic gains on GHG emissions and household food security in the Tanga region of Tanzania, estimating that genetic gains could reduce emissions intensity of milk by as much as 50%. However, their study only accounted for direct non-CO 2 emissions, and thus potentially omitted a significant component of the dairy C footprint occurring from LUC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, owing to the higher feed conversion efficiency and greater efficiency of Bos taurus genetics 88 , a greater uptake of Bos taurus in place of Bos indicus genetics could allow for milk production targets to be met with a smaller land and carbon footprint. Notenbaert et al 26 evaluated the role of genetic gains on GHG emissions and household food security in the Tanga region of Tanzania, estimating that genetic gains could reduce emissions intensity of milk by as much as 50%. However, their study only accounted for direct non-CO 2 emissions, and thus potentially omitted a significant component of the dairy C footprint occurring from LUC.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis sought evidence for the merits of linking the LMP to climate change mitigation initiatives, such as a dairy sector Nationally Appropriate Mitigation Action (NAMA). We used a life cycle assessment (LCA) to quantify GHG emissions adding on previous work by Mottet et al 23 , Brandt et al 24 , 25 and Notenbaert et al 26 . While all these studies accounted for the role of improved productivity in reducing direct dairy sector emissions, to date no study has evaluated specifically the role of land sparing and the potential for avoided land use change emissions to contribute to reductions in the dairy carbon footprint for Tanzania’s dairy.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to maximize production and profitability need to be balanced with long-term sustainability and environmental stewardship. It is therefore important to assess potential environmental impacts before embarking on large-scale development projects geared towards livestock production intensification and value chain transformation (Notenbaert et al 2020).…”
Section: Quantification Of Environmental Impacts and Trade-offs/synergiesmentioning
confidence: 99%
“…The application of the CLEANED tool to the dairy VC in Tanga, Tanzania (Notenbaert et al 2020), revealed that milk production increases associated with the introduction of improved feeding strategies are projected to go hand-in-hand with increases in land requirements for feed production and associated increases in absolute soil loss. Under unchanged fertility management systems, it would result in an increasing negative N balance.…”
Section: Quantification Of Environmental Impacts and Trade-offs/synergiesmentioning
confidence: 99%
“…Studies modeling the impacts of improved feeding as one of the CSA practices in livestock management found that planting improved forages for livestock can buffer seasonal crop losses due to climate variability, thereby contributing to households' resilience. Improved livestock feeding, with the use of different feedstocks or feeding practices, was also found to improve water use efficiency and increase land productivity (measured by the amount of land needed to produce the same milk yield as conventional practices), which has implications for mitigation as well in terms of lower emissions per unit of output (Notenbaert et al, 2020). However, several studies also highlighted the potential for an increase in absolute emissions even if efficiency improves due to herd expansion.…”
Section: Productivity Resilience and Mitigationmentioning
confidence: 99%